A Comparative Study of Pancreatic Acinar Cell Carcinoma: A Case–Control Study - Bor‐Shiuan Shyr; Ting‐Chung Chen; Shin‐E. Wang; Shih‐Chin Chen; Yi‐Ming Shyr; Bor‐Uei Shyr (Health Science Reports)
ABSTRACT Background and Aims Pancreatic acinar cell carcinoma (PACC) is rare. This study aims to elucidate its clinical features and survival outcomes. Methods Patients diagnosed with PACC were enrolled. A comparison between PACC and pancreatic ductal adenocarcinoma (PDAC) patients was conducted following propensity score matching (PSM). Results There were 11 resectable and nine unresectable PACC. The majority (60%) of PACC cases were located in the pancreatic head, with a median tumor size of 5.9 cm. Elevated serum lipase level was observed in 64.3% of cases. Regional lymph node involvement was found in 65.0%. The median survival was 20.0 months for resectable PACC patients compared to 6.7 months for unresectable cases. The 1‐, 3‐, and 5‐year survival rates were 100%, 49.1%, and 32.0%, respectively, for resectable PACC patients, while for unresectable cases, they were 33.3%, 0%, and 0%. Resectable PACC patients exhibited lower rates of lymph node involvement (36.4% vs. 66.1%), lymphovascular invasion (LVI), 36.4% versus 72.8%, and perineural invasion (PNI), 45.5% versus 86.0%, compared to PDAC. Following PSM, there was no significant difference in survival between resectable PACC and PDAC. Conclusion PACC is associated with lower rates of lymph node involvement, LVI, and PNI, which might attribute to superior outcome when compared with PDAC reported in the literature. However, there is no survival difference between resecrable PACC and PDAC after PSM.